2010
DOI: 10.1103/physrevb.82.184511
|View full text |Cite
|
Sign up to set email alerts
|

Electron correlation in the FeSe superconductor studied by bulk-sensitive photoemission spectroscopy

Abstract: We have investigated the electronic structures of recently discovered superconductor FeSe by soft-x-ray and hard-x-ray photoemission spectroscopy with high bulk sensitivity. The large Fe 3d spectral weight is located in the vicinity of the Fermi level (EF ), which is demonstrated to be a coherent quasi-particle peak. Compared with the results of the band structure calculation with local-density approximation, Fe 3d band narrowing and the energy shift of the band toward EF are found, suggesting an importance of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
48
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 53 publications
17
48
0
Order By: Relevance
“…Fig 2) corresponds to the experimentally obtained features at 0.1 eV and 0.5 eV, respectively. The discrepancy in the energy positions could be due to the self-energy correction which is neglected in the calculations [24]. The partial density of states (PDOS) for Fe 3d orbitals for an energy range 0 -2.5 eV is represented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fig 2) corresponds to the experimentally obtained features at 0.1 eV and 0.5 eV, respectively. The discrepancy in the energy positions could be due to the self-energy correction which is neglected in the calculations [24]. The partial density of states (PDOS) for Fe 3d orbitals for an energy range 0 -2.5 eV is represented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This orbital differentiation signals that the material is in the vicinity of an orbital selective Mott transition, as proposed previously for other iron pnictides [14], where xy orbital is effectively insulating while other orbitals remain metallic. In Fig.1(b) we also display mass enhancement extracted from optics [15][16][17][18] and ARPES [19][20][21][22][23][24] measurements, and notice a good agreement between our theory and experiment when available. The effective mass extracted from ARPES and optics should be compared with that of the t2g orbitals which contribute most of the spectral weight at low energy.…”
mentioning
confidence: 90%
“…The Fe spectrum has a single line, which is narrower than the corresponding line of FeSe1-yTey. This dominant line in the spectrum of FeSe1-yTey is slightly broader than that of Fe, perhaps owing to Se hybridization state in the lower-energy region (Yamasaki et al, 2010;Subede et al, 2008). Iron pnictides are weakly correlated systems, unlike high-Tc cuprates.…”
Section: Electron Correlations Of Fese1-yteymentioning
confidence: 99%
“…Photoemission spectroscopy (PES) measurements (A. Yamasaki et al, 2010) support the density of state (DOS) calculations on the FeSex system. These results indicate the Fe-Se hybridization and itinerancy with weak to moderate electronic correlations (Yoshida et al, 2009), while recent theoretical calculations have suggested strong correlations (Aichhorn et al, 2010;Pourret et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation